The effects of demography factors on ICT usage among form five Kedah religious school students / Noor Rasidah Ali …[et al.] - Ali, Noor Rasidah; Bidin, Samsiah; Abd Razak, Nor Hafizah; Muhamat Dawam, Siti Rafidah (Research Management Institute, 2013)
Integration of information and communication technology (ICT) in teaching and learning will be able to generate a positive impact in student’s academic achievement. Taking into consideration of this issue, government of Malaysia has taking an initiative by creating Malaysian Education Development Plan 2013 - 2025. Part of the plan is focusing on the needs of school infrastructure development for example at least 20 students will be equipped with ICT in all schools. In Malaysia education mainstream, besides having Sekolah Rendah Kebangsaan (SRK) or Sekolah Menengah Kebangsaan (SMK), there is also Sekolah Agama Bantuan Kerajaan (SABK). SABK is one of the government efforts to help and strengthen the religious schools in Malaysia. Since ICT usage has becoming global phenomena, Sekolah Agama Bantuan Kerajaan (SABK) also tries to adapt this approach in their teaching and learning process. In accordance to that, five Sekolah Rendah Agama (SRA) under management of Jabatan Agama Islam Wilayah Persekutuan (JAWI) has been selected as pilot schools in utilizing ICT for teaching and learning. In this research work, the significance of conducting the project is to discover the effect of students’ demographic profile on the level of ICT usage. It will be done by identifying the effects of different family demographic profile on students’ ICT usage. Other than that, level of ICT facilities available to the students are also investigated.